Pengaruh Beban Kerja Terhadap Kepuasan Kerja Karyawan PT Sicepat Ekspres Cabang Bima - Asrafiansyah Asrafiansyah; Muhammad Yusuf (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
In the era of globalization which is growing rapidly, the flow of communication and technology between two or more parties is getting smoother and more sophisticated. Companies must be able to take opportunities in this globalization era to develop their companies, because competition between companies is getting tougher. However, it is inseparable from the development of communication and technology, employees who participate actively in developing the company. Employees hold one important factor in determining the success or failure of the development process of the company itself. However, there is also one way that can minimize the probability of failure in the development of a company, namely management.